Kuguacin J isolated from Momordica charantia leaves inhibits P-glycoprotein (ABCB1)-mediated multidrug resistance - Pornsiri Pitchakarn (2018)
Multidrug resistance (MDR) is a major factor in the failure of chemotherapy in cancer patients. Resistance to chemotherapy has been correlated to the overexpression of ABC drug transporters including P-glycoprotein (P-gp) that actively efflux chemotherapeutic drugs from cancer cells. Our previous study showed that bitter melon (Momordica charantia) leaf extract (BMLE) was able to reverse the MDR phenotype by increasing the intracellular accumulation of chemotherapeutic drugs. In the present study, bioguided fractionation was used to identify the active component(s) of BMLE that is able to modulate the function of P-gp and the MDR phenotype in a human cervical carcinoma cell line (KB-V1). We found that kuguacin J, one of the active components in BMLE, increased sensitivity to vinblastine and paclitaxel in KB-V1 cells. A flow cytometry assay indicated that kuguacin J inhibits the transport function of P-gp and thereby significantly increases the accumulation of rhodamine 123 and calcein AM in the cells. These results were confirmed by [3H]-vinblastine transport assay. Kuguacin J significantly increases intracellular [3H]-vinblastine accumulation and decreased the [3H]-vinblastine efflux in the cells. Kuguacin J also inhibited the incorporation of [125I]-iodoarylazidoprazosin into P-gp in a concentration-dependent manner, indicating that kuguacin J directly interacts with the drug-substrate-binding site on P-gp. These results indicate that kuguacin J modulates the function of P-gp by directly interacting at the drug-substrate-binding site, and it appears to be an effective inhibitor of P-gp activity in vitro and thus could be developed as an effective chemosensitizer to treat multidrug-resistant cancers. © 2012 Elsevier Inc.